2019
DOI: 10.1021/acs.iecr.8b06062
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Pool Boiling Runs: A Controlled Process to Form Reduced Graphene Oxide Surfaces from Graphene Oxide with Tunable Surface Chemistry and Morphology

Abstract: Wettability and wickability of a surface are the key properties that govern a variety of industrial applications. Understanding the effect of aging on the durability of these surfaces and subsequent changes occurring in their molecular structure is vital to maintain functionality. In this work, we used repetitive pool boiling to test the durability of graphene oxide-copper (GO-Cu) coated surfaces and studied subsequent changes in surface chemistry and morphology. We observed the transformation of GO-Cu to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The change in wetting behavior was observed for the coating after 3 repetitive boiling tests. A similar change in wetting properties was also observed for our previous work 28 involving graphene-based coatings and is attributed to the removal of oxygen groups from graphene due to repetitive boiling. Despite small reduction in the pool boiling performance, strong adhesion between the coating and the substrate was observed.…”
Section: Enhanced Heat Transfer Properties During the Pool Boiling Prsupporting
confidence: 86%
See 2 more Smart Citations
“…The change in wetting behavior was observed for the coating after 3 repetitive boiling tests. A similar change in wetting properties was also observed for our previous work 28 involving graphene-based coatings and is attributed to the removal of oxygen groups from graphene due to repetitive boiling. Despite small reduction in the pool boiling performance, strong adhesion between the coating and the substrate was observed.…”
Section: Enhanced Heat Transfer Properties During the Pool Boiling Prsupporting
confidence: 86%
“…Additionally, static wettability and dynamic wicking of sintered surfaces were measured for the surfaces using a VCA Optima Goniometer contact angle measurement instrument. For dynamic wicking, a distilled water droplet of 2 µL was steadily brought into contact with the coated surfaces using a static sessile drop method and liquid propagation was recorded using a high-speed camera 28 .…”
Section: Methods Copper Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…We further confirmed the long-term sustainability on microscale coatings by conducting multiple boiling tests that drastically improved heat transfer coefficient. This resulted from the transition of superhydrophilic to superhydrophobic coatings supported by Fourier transform infrared, (FTIR) studies that confirmed the removal of hydroxyl-based functional groups from the surfaces (Rishi et al, 2019a;Rishi et al, 2019b).…”
Section: Introductionmentioning
confidence: 97%
“…The distinctive structure of a single layered sp 2 -hybridized carbon atoms endows the thinnest material known as graphene, which has gained an enormous attention in various industrial applications such as surface coatings [1][2][3][4] , electronics [5,6] , energy storage [7,8] , lithium-ion batteries [9][10][11][12] , automotive [13,14] , and aerospace sector [15][16][17] due to its exceptional electrical, thermal, and mechanical properties [18] . Owing to very high thermal conductivity, graphene has also been implemented in thermal interface materials [19,20] , nanofluids [21] , and composite coatings [22][23][24] for heat transfer applications that require high heat flux dissipation [25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%